Gender-based violence in healthcare institutions - legal response to gynecological and obstetrical violence - Simic, Jelena (Temida, 2025)
Despite advancements in recent decades, various forms of violence against women persist, albeit in very different ways. Mistreatment and violence directed toward women?s bodies extend to the field of medicine, and gynecological and obstetric practices are not immune to such misconduct. Gynecological and obstetric violence is an umbrella term that encompasses a variety of demeaning, violent, and harmful practices perpetrated during all types of gynecological and obstetric care. This includes institutional and personal attitudes that lead to the violation of women?s autonomy, human rights, and sexual and reproductive health. Despite various international legislative initiatives and recommendations from the World Health Organisation addressing disrespectful and abusive treatment, gynecological and obstetric violence is still poorly known to Serbian public opinion and control over women?s bodies is still deeply rooted in Serbian society. This paper aims to provide a brief outline of the systemic and widespread nature of gynecological and obstetric violence, and to make recommendations to national decision-makers to tackle this form of violence.